Identification and Analysis of MYB Gene Family for Discovering Potential Regulators Responding to Abiotic Stresses in Curcuma wenyujin - Wei, Qiuhui; Liu, Yuyang; Lan, Kaer; Wei, Xin; Hu, Tianyuan; Chen, Rong; Zhao, Shujuan; Yin, Xiaopu; Xie, Tian (Frontiers in Genetics, 2022)
MYB superfamily is one of the most abundant families in plants, and plays critical role in plant growth, development, metabolism regulation, and stress response. Curcuma wenyujin is the main source plant of three traditional Chinese medicines, which are widely used in clinical treatment due to its diverse pharmacological activities. In present study, 88 CwMYBs were identified and analyzed in C. wenyujin, including 43 MYB-related genes, 42 R2R3-MYB genes, two 3R-MYB genes, and one 4R-MYB gene. Forty-three MYB-related proteins were classified into several types based on conserved domains and specific motifs, including CCA1-like type, R-R type, Myb-CC type, GARP-like type, and TBR-like type. The analysis of motifs in MYB DBD and no-MYB regions revealed the relevance of protein structure and function. Comparative phylogeny analysis divided 42 R2R3-MYB proteins into 19 subgroups and provided a reference for understanding the functions of some CwMYBs based on orthologs of previously characterized MYBs. Expression profile analysis of CwMYB genes revealed the differentially expressed genes responding to various abiotic stresses. Four candidate MYB genes were identified by combining the results of phylogeny analysis and expression analysis. CwMYB10, CwMYB18, CwMYB39, and CwMYB41 were significantly induced by cold, NaCl, and MeJA stress treatments. CwMYB18 and CwMYB41 were proved as regulators with activity of transcriptional activation, whereas CwMYB39 and CwMYB10 were not. They may participate in the response to abiotic stresses through different mechanisms in C. wenyujin. This study was the first step toward understanding the CwMYB family and the response to abiotic stresses in C. wenyujin.